(untitled) (Communications in Mathematical Research, 2021)
In this paper we discuss normal functions concerning shared values. We obtain the following result. Let F be a family of meromorphic functions in the unit disc ∆, and a be a nonzero finite complex number. If for any f ∈F, the zeros of f are of multiplicity, f and f′ share a, then there exists a positive number M such that for any f ∈ F, (1 − |z|^2 ) |f′(z)|1 + |f(z)|^2 ≤ M.